HUBUNGAN KECERDASAN EMOSIONAL DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Rahayu Sri Ningsih; Mohamad Rif'at; Agung Hartoyo (UNIVERSITAS TANJUNGPURA, 2021)
This research aims to know between emotional intelligence and mathematic’s problem-solving in students grade 8th in MTs. Al-Fathaanah Mempawah. This research used the correlation to be method and use the Pearson product moment’s formula to processing data. Twenty-one students are samples of this research, and they are select by using purposive sampling. The data collection technique in this research is using problem-solving and indirect communication that was using an emotional intelligence questionnaire. This research is the connection of emotional intelligence with mathematics problem-solving students grade 8th on MTs. Al-Fathaanah Mempawah, with r = 0.45 and the correlation classified is average. Keywords: Emotional Intelligence, Mathematical Problem Solving Ability